Fatigue in Multiple Sclerosis: A Look at the Role of Poor Sleep - Strober, Lauren B. (Frontiers in Neurology, 2015)
Fatigue is a frequent and debilitating symptom of multiple sclerosis (MS) with rates ranging anywhere from 53% to 90%. Despite its high prevalence and grave impact on overall functioning and quality of life, the accurate definition, quantification, and etiology of fatigue has plagued the MS literature and clinical care for decades. With regard to its etiology, MS-related fatigue has been construed as being either primary or secondary. Primary fatigue is purported to be related to centrally mediated processes of the disease whereas secondary fatigue is thought to be a result of the host of factors that may accompany MS (e.g., depression, sleep disturbance). The present paper focuses on secondary fatigue and the role of sleep disturbance, in particular. Despite the intuitive assumption that sleep problems could contribute to fatigue, sleep problems in MS have gone fairly unrecognized until recently. The present paper provides a brief review of the literature pertaining to the prevalence and nature of sleep problems in MS as well as their association with fatigue. A replication of this author’s and others work is also presented, further demonstrating that sleep disturbance is a significant contributor to fatigue in MS when taking into account disease variables, depression, and sleep disturbance. Finally, a discussion of the role of effective treatment of sleep problems on fatigue is provided.